Α‐Helices propagating from stable nucleators exhibit unconventional thermal folding. Issue 23 (10th November 2021) - Pal, Sunit; Banerjee, Shreya; Prabhakaran, Erode N.
Abstract : Although the effect of thermal perturbations on protein structure has long been modeled in helical peptides, several details, such as the relation between the thermal stabilities of the propagating and nucleating segments of helices, remain elusive. We had earlier reported on the helix‐nucleating propensities of covalent H‐bond surrogate‐constrained α‐turns. Here, we analyze the thermal stabilities of helices that propagate along peptides appended to these α‐helix nucleators using their NMR and far‐UV CD spectra. Unconventional thermal folding of these helix models reveals that the helical fold in propagating backbones resists thermal perturbations as long as their nucleating template is intact. The threshold temperature of such resistance is also influenced by the extent of similarity between the natures of helical folds in the nucleating and propagating segments. Correlations between helicities and rigidities of helix‐nucleating and helix‐propagating segments reveal subtle interdependence, which explains cooperativity and residual helix formation during protein folding. Abstract : Unconventional thermal folding behavior exhibited in helix models—whose synthetic helix‐nucleating domains are unperturbed by temperature—reveals that the helical fold in propagating backbones resists thermal perturbations as long as their nucleating template is intact. The threshold temperature of such resistance is influenced by the extent of similarity between the natures of helical folds in the nucleating and propagating segments.